KARAKTERISTIK CUKA DARI CAIRAN PULPA HASIL SAMPING FERMENTASI BIJI KAKAO (Theobroma cacao L.) PADA PERLAKUAN PENAMBAHAN INOKULUM Acetobacter aceti DAN LAMA FERMENTASI - Bhusana Dasa, Yudisthira Dharma; Ganda Putra, G.P.; Wayan Gunam, I.B. (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI, 2017)
This aims to this study were to (1) determine the effect of addition inoculum Acetobacter aceti and fermentation period on the characteristics of vinegar fermentation from liquid waste of cocoa beans fermentation, and (2) to determine the accurate of addition innoculum Acetobacter aceti and fermentation period which one produces the best characteristic fermentation from liquid waste of cacao beans fermentation. The experiments was designed by a Split Plot design with the addition of inoculum Acetobacter aceti into the main plot consisting of 3 plots 10%. 15%. and 20% (v/v). Fermentation period is a subplots consisting of 6 levels were 0. 5. 10. 15. 20. 25 days. The fermentation period was affected significantly (P <0,01) on levels of acetic acid, alcohol content and total dissolved solids from a liquid pulp vinegar fermentation from liquid waste of cacao beans fermentation, while the addition of inoculum Acetobacter aceti and interaction did not affect (P> 0,05). The best characteristics of fermentation vinegar was found on the addition of an inoculum of 20% and fermentation period for 25 days with the acetic acid content, alcohol content and total of soluble solid were 3.21 (% v/v), 0.00%, and 4.79 oBrix. respectively.